Bio‐inspired optimization for electromagnetic structure design using full‐wave techniques on GPUs. (28th January 2013) - Kilic, O.; El‐Araby, E.; Nguyen, Q.; Dang, V.
SUMMARY: The electromagnetic modeling of antennas and radio frequency devices has become increasingly challenging as the applications demand intricate and complex designs, such as fine features embedded in electrically large structures or integrated systems (e.g., antennas on vehicles). Often the design stage is further challenged by the need to find an optimal solution, which results in a numerically intensive problem. The objective of this paper is to investigate the use of graphics processing units (GPUs) in such challenging design and optimizations. Two full‐wave approaches (method of moments and rigorous coupled wave analysis) are discussed along with a bio‐inspired optimization technique, namely the particle swarm optimization. The inherent parallel nature of the GPUs is utilized in implementing the most numerically intensive parts of these full‐wave methods. Furthermore, the independent search mechanism employed by the particle swarm optimization in its agent‐based search renders itself to parallelism offered by GPUs. The paper demonstrates the acceleration achieved by the GPUs in designing a variety of radio frequency structures such as reconfigurable patch antennas and antireflective surfaces. Copyright © 2013 John Wiley & Sons, Ltd.